Diatomite with gold nanoparticles for atrazine adsorption - Melany Aguilar; Sarah Briceño; Karla Vizuete; Alexis Debut; Carlos Reinoso; Gema González (Carbon Trends)
Atrazine is a commonly used herbicide worldwide, and it has significant environmental concerns due to its toxic ecological effects. This work uses diatomite decorated with gold nanoparticles to evaluate its capacity for atrazine adsorption. The structural characterization was studied by Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), Energy Dispersive spectroscopy (EDX), Fluorescence microscopy and X-ray photoelectron spectroscopy (XPS). Our findings reveal that diatomite decorated with gold nanoparticles with an average particle size of 10 nm enhances the Raman signal and fluorescence intensity for atrazine detection. Experimental conditions, such as atrazine concentration, pH, contact time, and diatomite mass, have been optimized to quantify the maximum removal conditions using ultraviolet–visible spectroscopy, reaching a maximum adsorption of 2.5 mg/g in 4 h. FTIR and XPS evidence the interaction of the amine groups of the atrazine with the diatomite-decorated surface. The impact of this work relies on environmental remediation using naturally available diatomite decorated with gold nanoparticles and understanding the binding interactions for the removal of atrazine.